What GDPR tells about certification. Issue 38 (September 2020) - Lachaud, Eric
Abstract: The EU lawmaker has introduced several certification models in the GDPR. A first model entitles accredited private certification bodies to design and manage certification schemes under the close monitoring of the supervisory authorities. Another model gives to the supervisory authorities the opportunity to design and manage their own schemes. The EU lawmaker has also left the door open to the establishment of schemes at the margin of the data protection framework. Nothing in the GDPR prohibits to create certification schemes outside Articles 42/43 regime. The diversity of arrangements shows that certification is a flexible system capable of adapting to many different situations and environments. This is also a free market that proves to be difficult, if not impossible, to entirely monitor. These basic features challenge the attempt of the EU lawmaker to monitor the design and management of certification schemes in the GDPR. The GDPR also tells that the definition of certification suggested by the European Data Protection Board does not fully map this notion as designed in the GDPR. The data protection regulation offers a much more detailed picture of certification than the one proposed by the European Data Protection Board. The GDPR shows that the nature of certification is driven by the context in which this instrument is used. The analysis of the monitoring process of the codes of conduct set in Article 41 GDPR contributes, by contrast, to clarify the very nature certification. It shows that this is neither the attestation of conformity nor the conformity assessment that best defines certification.